INTERTEXTUAL ANALYSIS OF PROPHET MUSA’S STORY (Q.S. AL-BAQARAH 67-71) AND ITS RELEVANCE TO CONTEMPORARY ISLAMIC COMMUNICATION AND DA'WAH - Taufiq, Muhammad (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
ABSTRACTThis study examines the story of Prophet Musa in Q.S. Al-Baqarah 67–71 through Angelika Neuwirth’s intertextuality perspective, connecting it to Prophet Muhammad's preaching in Medina. The narrative emphasizes obedience, sincerity, and patience, which are essential for fostering multicultural societies. Using a qualitative descriptive-analytic approach, this research explores the interplay between Qur'anic narratives and other religious traditions, such as Judaism. The findings reveal that the command to sacrifice a cow conveys profound universal moral messages, such as the importance of compliance and sincerity in religious practices. These values are mirrored in Prophet Muhammad’s wisdom-, dialogue-, and empathy-based preaching strategies, particularly in addressing Medina's diverse community. This study contributes to Qur'anic studies by offering an intertextual perspective and practical guidance for contemporary Islamic preaching strategies that prioritize inclusivity and contextual relevance. Keywords: intertextuality, Q.S. Al-Baqarah 67-71, Prophet Musa, Prophet Muhammad, universal values, preaching strategies.